login
This site is supported by donations to The OEIS Foundation.

 

Logo

Invitation: celebrating 50 years of OEIS, 250000 sequences, and Sloane's 75th, there will be a conference at DIMACS, Rutgers, Oct 9-10 2014.

Hints
(Greetings from The On-Line Encyclopedia of Integer Sequences!)
A087204 Period 6: repeat 2,1,-1,-2,-1,1. 6
2, 1, -1, -2, -1, 1, 2, 1, -1, -2, -1, 1, 2, 1, -1, -2, -1, 1, 2, 1, -1, -2, -1, 1, 2, 1, -1, -2, -1, 1, 2, 1, -1, -2, -1, 1, 2, 1, -1, -2, -1, 1, 2, 1, -1, -2, -1, 1, 2, 1, -1, -2, -1, 1, 2, 1, -1, -2, -1, 1, 2, 1, -1, -2, -1, 1, 2, 1, -1, -2, -1, 1, 2, 1, -1, -2, -1, 1, 2, 1, -1, -2, -1, 1, 2, 1, -1, -2, -1, 1, 2, 1, -1, -2, -1, 1, 2, 1, -1, -2, -1, 1 (list; graph; refs; listen; history; text; internal format)
OFFSET

0,1

COMMENTS

Satisfies (a(n))^2 = a(2n) + 2. Shifted differences of itself.

Multiplicative with a(2^e) = -1, a(3^e) = -2, a(p^e) = 1 otherwise. David W. Wilson Jun 12, 2005.

Moebius transform is length 6 sequence [ 1, -2, -3, 0, 0, 6]. - Michael Somos, Oct 22 2006

REFERENCES

A. T. Benjamin and J. J. Quinn, Proofs that really count: the art of combinatorial proof, M.A.A. 2003, id. 176.

LINKS

Table of n, a(n) for n=0..101.

Tanya Khovanova, Recursive Sequences

Wikipedia, Lucas sequence

Index entries for recurrences a(n) = k*a(n - 1) +/- a(n - 2)

Index to sequences with linear recurrences with constant coefficients, signature (1,-1).

FORMULA

a(n) = a(n-1) - a(n-2), starting with a(0) = 2 and a(1) = 1.

G.f.: (2-x)/(1-x+x^2).

a(n) = Sum(k>=0, (-1)^k*n/(n-k)*C(n-k, k)).

a(n) = (1/2)*((-1)^floor(n/3) + 2*(-1)^floor((n+1)/3) + (-1)^floor((n+2)/3)).

a(n) = -(1/6)*((n mod 6)+2*((n+1) mod 6)+((n+2) mod 6)-((n+3) mod 6)-2*((n+4) mod 6)-((n+5) mod 6)). - Paolo P. Lava, Oct 09 2006

a(n) = a(-n)=-a(n-3). - Michael Somos, Oct 22 2006

E.g.f. 2*exp(x/2)*cos(sqrt(3)*x/2) = 2*G(0) where G(k)= 1 + x/(2*(3*k+1) + 2*x*(3*k+1)/( 3*k+2 - x - 2*x*(3*k+2)/(2*x + 3*(k+1)/G(k+1)))); (continued fraction, 3rd kind, 4-step). - Sergei N. Gladkovskii, Aug 12 2012

a(n) = r^n + s^n, with r=(1+i*sqrt(3))/2 and s=(1-i*sqrt(3))/2 the roots of 1-x+x^2. - Ralf Stephan, Jul 19 2013

EXAMPLE

a(2) = -1 = a(1) - a(0) = 1 - 2 = ((1+sqrt(-3))/2)^2 + ((1-sqrt(-3))/2)^2 = -1 = -2/4 + 2sqrt(-3)/4 - 2/4 -2 sqrt(-3)/4 = -1.

MATHEMATICA

PadLeft[{}, 108, {2, 1, -1, -2, -1, 1}] (* Harvey P. Dale, Sep 11 2011 *)

PROG

(PARI) {a(n)=[2, 1, -1, -2, -1, 1][n%6+1]} /* Michael Somos, Oct 22 2006 */

(Sage) [lucas_number2(n, 1, 1) for n in xrange(0, 102)]# [From Zerinvary Lajos, Apr 30 2009]

CROSSREFS

Essentially the same as A057079 and A100051. Pairwise sums of A010892.

Sequence in context: A131556 A107751 A132367 * A101825 A177702 A131534

Adjacent sequences:  A087201 A087202 A087203 * A087205 A087206 A087207

KEYWORD

sign,easy,mult

AUTHOR

Nikolay V. Kosinov (kosinov(AT)unitron.com.ua), Oct 19 2003

EXTENSIONS

Edited by Ralf Stephan, Feb 04 2005

STATUS

approved

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Transforms | Superseeker | Recent | More pages
The OEIS Community | Maintained by The OEIS Foundation Inc.

Content is available under The OEIS End-User License Agreement .

Last modified August 22 11:20 EDT 2014. Contains 245954 sequences.